Production potential of aluminium tolerant lines of lentil - Singh, Dharmendra; Dikshit, H. K.; Nongthombam, Rita; Chongtham, Nandini; Singh, N. Tomba; Singh, M. P. (Indian Farming, 2015)
The Indian Agricultural Research Institute, New Delhi has developed lentil lines that have significant contribution for aluminium stress conditions. These lines provided higher yield than that of check variety L-4076 in detailed field trials conducted at various locations of North Eastern Region under Central Agricultural University, Imphal, (Manipur) and ICAR Research Complex for NEH region, A.P. Center, Basar (Arunachal Pradesh). As a result, such developed lines have been identified for cultivation in the acid affected regions of the country.